Problems of Paraphrase: Bottom's Dream - David Hills (Baltic International Yearbook of Cognition, Logic and Communication, 2007)
Philosophers and critics alike often contend that metaphors cannot or should not be paraphrased, ever. Yet a simple and decisive empirical argument — The Horse’s Mouth Argument—suffices to show that many metaphors can be paraphrased without violating the spirit in which they were put forward in the first place. This argument leaves us with urgent unanswered questions about the role of paraphrase in a more inclusive division of exegetical labor, about the tension between its notorious openendedness and its claim to restate something already stated, andabout the relation between the content of a paraphrase and the content (or contents) of the metaphor the paraphrase purports to explain. But it leaves us in a position to state such questions more clearly and hopefully than we could before.
Keywords: philosophy; linguistic